Semantics of wh-questions with the verbal how in mandarin - Dong, Hongyuan (Proceedings of the Amsterdam Colloquium, 2007)
This paper studies wh-questions with the verbal “zenme”(“how”) in Mandarin, e.g. “Yuehan zenme-le Mali?”, a literal English translation of which is “John how-ed Mary?” First I give a semantic analysis of the denotation of such questions, arguing that the verbal “how” quantifies over properties of events. Second I give a compositional semantics of such wh-questions, based upon works by Berman (1994) and Lahiri (2002). Third, I discuss the meanings of the use of this “how” as zero-place, one-place, and two-place verbs, and argue that “how” is uniformly used as a two-place/transitive verb, and this explains some properties of such “how” questions.